2015
DOI: 10.17261/pressacademia.2015211506
|View full text |Cite
|
Sign up to set email alerts
|

A research about the relationship of psychological safety and organizational politics perception with compulsory citizenship behavior and the pressures behind compulsory citizenship behavior

Abstract: The main purpose of this study is to examine the relationship of Psychological Safety (PS) and Organizational Politics Perception (OPP) with Compulsory Citizenship Behavior (CCB). In order to investigate whether CCB exists or not in Turkish institutions, 27 item-OCB scale is considered with its dimensions and asked with an introduction that whether the respondents have experienced any pressure for displaying these behaviors. Moreover, the potential pressures such as respondents' oneself, family, coworkers, org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 48 publications
2
14
1
3
Order By: Relevance
“…This finding is in line with previous studies (Ahmadian et al, 2017;Vigoda-Gadot, 2007). The study by Alkan (2015) confirmed that organisational politics were positively correlated with compulsory citizenship behaviour. In other words, employees who were working in a political working environment tended to unwillingly handle extra-roles.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is in line with previous studies (Ahmadian et al, 2017;Vigoda-Gadot, 2007). The study by Alkan (2015) confirmed that organisational politics were positively correlated with compulsory citizenship behaviour. In other words, employees who were working in a political working environment tended to unwillingly handle extra-roles.…”
Section: Discussionsupporting
confidence: 93%
“…Ahmadian et al (2017) found that organisational politics make a positive contribution toward compulsory citizenship behaviour. This finding is also in accordance with findings by Alkan (2015).…”
Section: G Organisational Politicssupporting
confidence: 94%
See 1 more Smart Citation
“…Yapılan analizler sonucunda ortaokul öğretmenlerinin örgütsel vatandaşlık davranışlarındaki varyansın yaklaşık % 7'sinin örgütsel politika algılarında meydana gelen değişimle açıklanabildiği, öğretmenlerin örgütsel politika algısının örgütsel vatandaşlık davranışlarını negatif yönde anlamlı bir şekilde yordadığı sonuçlarına ulaşılmıştır. Bu araştırmadan elde edilen sonuçlar ilgili araştırma sonuçlarıyla benzerlik göstermektedir (Afshardoust ve diğerleri, 2013;Alkan, 2015;Bedi ve Schat, 2013;Faye ve Long, 2014;Maslyn ve Fedor, 1998). Örgütsel vatandaşlık davranışı ile örgütsel politika algısı arasındaki ilişki örgütsel bağlılıkta olduğu gibi sosyal değişim ve yatırım teorisi ile açıklanmaktadır (Cropanzano ve diğerleri, 1997;Wilson, 2000).…”
Section: Sonuç Tartişma Ve öNeri̇lerunclassified
“…An employee behavior has been a focus of concern for practitioners and scholars because it is relatively difficult to predict, determine and measure behavior. Prior research has studied citizenship behavior as a multi-dimensional construct which has its positive outcomes in terms of organizational citizenship behavior (LePine, Erez, & Johnson, 2002;Luthans& Youssef, 2007;Podsakoff et al, 2009) and negative outcomes in terms of compulsory citizenship behavior (Vigoda-Gadot, 2007;Zhao et al, 2014;Alkan & Turgut, 2015). The prevalent literature has clearly made distinctions between these two constructs based on the former being a voluntary helping behavior, and the latter being a forced involuntary behavioral outcome (Ahmad & Khan, 2016;Vigoda-Gadot, 2007).…”
Section: Introductionmentioning
confidence: 99%